The Role of Financial Institutions In Financial Inclusion in the Krupuk Industry SMEs The Karangmluwo Mangli Kaliwates Community, Jember - Siti Masrohatin; Hikmatul Hasanah; Indra Kusumawati; Tri Kurniawati Retnaningsih (Al-Kharaj: Journal of Islamic Economic and Business, 2023)
The objective of the financial inclusion program is to eliminate all forms of barriers to public access to the use of financial services supported by existing infrastructure. Thus the SMEs community will easily overcome the problem of lack of capital by getting easy financing services from banks, in this study conducted on the SMEs community in the Karangmluwo cracker industry. However, can the SMEs community of the Karangmluwo cracker industry as a whole be able to feel the benefits of the financial inclusion program? Until this research formulated the formulation of the problem: What is the role of financial institutions in financial inclusion in the Karangmluwo cracker industry SMEs?, what are the arguments of the Karangmluwo cracker industry community who are reluctant to collaborate with financial institutions? crackers Karangmluwo?. This study uses a descriptive qualitative approachand the results of research on several SMEs in the cracker industry of the Karangmluwo community, Mangli Kaliwates Jember, show that the benefits of the financial inclusion program are still not evenly distributed, it is proven that there are still Karangmluwo cracker industry communities who are reluctant to collaborate with financial institutions because of the complicated requirements and lack of socialization from the financial institutions. However, there are also some industrial communities in Karangmluwo who can benefit from this financial inclusion